AKTIVITAS PEMUDA DALAM MENGEMBANGKAN PENDIDIKAN ISLAM DI DESA LARANGAN DALAM PAMEKASAN - anisah isnaini (Ulumuna: Jurnal Studi Keilsman, 2017)
Advances in information technology certainly have an impact on its users. Youths who are still confused about finding their identity will try to explore and then adopt a style that they think is cool, they cannot avoid these technological advances but can choose which ones have a good impact on themselves, and this is where the function of Islamic education as a filter is to take the good and avoid the bad. Youth will play a role in the development of knowledge if it is functionally developed as a teacher in the environment where they live, especially in an environment that is backward in science and religion. This is in accordance with the opinion that says that the future of a nation is in the hands of youth, so that youth should be given the opportunity and opportunity to develop their potential and fill their independence by developing Islamic education. This study aims to determine how youth activities in developing Islamic education in the village of Larangan Dalam in Pamekasan. This research use desciptive qualitative approach. Data collection was carried out by means of interviews, observation and documentation study. The research was conducted in the village of Larangan Dalam in the sub-district of the Larangan, the district of Pamekasan. Based on the results of the study, it was found that: youth activities had a contribution in developing Islamic education both individually and in groups of organizations, while several organizations in the Larangan Dalam village were: ipnu-ippnu, youth mosques, and Karang Taruna.